OPTIMAL CONTROL AND DISCRETE-TIME MODELLING OF ALCOHOL MODEL WITH PHYSICAL AND PSYCHOLOGICAL COMPLICATIONS. (2020) - KHAJJI, BOUCHAIB; MOUMINE, EL MEHDI; FERJOUCHIA, HANANE; BALATIF, OMAR; RACHIK, MOSTAFA
No abstract available